FIRST RECORD OF THE WILT AND DEATH DISEASE ON DATE PALM TISSUE CULTURE CLONES OFFSHOOTS IN BASRAH PROVINCE –IRAQ - & et al., Al-Saad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Wilt death disease on date palm tissue culture offshoots is a new interested phenomenon observed in Iraq since a several years, represented by fungal disease infecting plants in pots and/or soil, causing graduate wilt starts from down fronds to the top, ending with death.  The survey results revealed that infection percentage ranged from 4% in Abulkhaseeb district to 4.5% in Al-Seeba area with no significant differences among infected orchards (P-0.369), while the death percentage was 6.2% in Al-Seeba area comparing with 2.4% Abulkhaseeb with no significant differences too (P=0.368). The isolation results confirmed that Fusarium solani was the main isolated fungus from all root samples. Five isolates of F.solani (MLA5, MLA6, MLA7, MLA9 and MLA10) were identified at morphological and molecular levels then deposited in NCBI gene bank under the registration numbers (MG932641.1-MG932645.1). The present study recorded F.solani as a causal fungus of wilt and death disease on date palm tissue culture offshoots for the first time in Iraq.